TRANSFORMATIONAL LEADERSHIP OF SCHOOL PRINCIPALS TO ENHANCE ISLAMIC EDUCATIONAL MANAGEMENT IN FORMAL INSTITUTIONS - Fakhri, Muh Dzulfiqar Faishal; Narimo, Sabar (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
This study aims to examine how school principals innovate in their leadership to improve the quality of Islamic education management in formal institutions. A qualitative research method was employed. Data were collected through a literature review, drawing from various sources, contexts, and approaches. The findings indicate that principals who effectively enhance the quality management of education are those who recognize themselves as leaders and are capable of managing the human resources within their institutions—such as teaching staff, students, and the entire academic community. Effective management of infrastructure and facilities in formal educational institutions is also essential. The study concludes that the role of leadership in formal educational institutions is crucial for improving Islamic education management. A leader must simultaneously fulfill multiple roles: as a leader, manager, supervisor, administrator, innovator, educator, and motivator.